2009
DOI: 10.1016/j.jacc.2008.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide Reduces Infarct Size and Improves Cardiac Function in a Porcine Model of Ischemia and Reperfusion Injury

Abstract: These data identify exenatide as a potentially effective compound to reduce infarct size in adjunction to reperfusion therapy in patients with acute MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
334
2
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(361 citation statements)
references
References 33 publications
15
334
2
10
Order By: Relevance
“…A functional GLP‐1 receptor (GLP‐1R) is highly expressed in the heart. GLP‐1R agonists and DPP‐4 inhibitors have beneficial effects on the cardiovascular system (Ban et al., 2008; Noyan‐Ashraf et al., 2009; Timmers et al., 2009). Previous studies have shown that GLP‐1 and its analogs protected the heart against ischemia‐reperfusion injury and diabetes mellitus (Tate, Robinson, Green, McDermott & Grieve, 2016; Wang et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A functional GLP‐1 receptor (GLP‐1R) is highly expressed in the heart. GLP‐1R agonists and DPP‐4 inhibitors have beneficial effects on the cardiovascular system (Ban et al., 2008; Noyan‐Ashraf et al., 2009; Timmers et al., 2009). Previous studies have shown that GLP‐1 and its analogs protected the heart against ischemia‐reperfusion injury and diabetes mellitus (Tate, Robinson, Green, McDermott & Grieve, 2016; Wang et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These drugs lower glucose levels by inhibiting the secretion of glucagon, promoting the release of insulin in response to hyperglycemia, slowing gastric emptying, and augmenting satiety. 14 On the basis of some evidence of cardioprotection in preliminary studies in animal models 15,16 and in pilot studies of myocardial ischemia 17,18 and heart failure in humans, 19 it was postulated 20,21 that in addition to improving glycemic control and promoting weight loss, GLP-1-receptor agonists may improve cardiovascular outcomes.…”
mentioning
confidence: 99%
“…Paradoxically, following meta-analytic data suggesting an increased cardiovascular risk with rosiglitazone [6], this class of agents has now undergone more rigorous long-term cardiovascular study, and the overall conclusion is that the long-term risk-benefit profile of these drugs is uncertain. The problem for newer agents such as incretin-based treatments, which have shown very promising effects in animal studies [7,8] and surrogate effects in clinical trials [9], is that solid evidence from long-term clinical trials will not be available for several years, as is the case with any newer agent that appears on the horizon.…”
mentioning
confidence: 99%